Delisted versus voluntary delisted versus remain listed: an ordered analysis - D. Balios; N. Eriotis; S. Missiakoulis; D. Vasiliou (Applied Economics Letters, 2015)
Public companies were classified according to whether they remain public or they have been delisted voluntarily or not. Proxy variables were separated according to accounting and/or market information and an ordered polytomous logit model was then applied in order to estimate the probability of delisting. Companies with poor liquidity, high leverage, big stock price decline and lack of interest from investors’ point of view (low trading activity) have higher probability to be delisted, voluntarily or not.